DOING SOCIO-LEGAL RESARCH IN DESIGN MODE - Perry-Kessaris, Amanda ([S.l.] : ROUTLEDGE, 2021)
This book is the first to explore what design can do for sociolegal research. It argues that designerly ways--mindsets that are practical, critical and imaginative, experimental processes and visible and tangible communication strategies--can be combined to generate potentially enabling ecosystems, and that within these ecosystems the abilities of a researcher to make meaningful contributions and to engage in meaningful research relations, both within our research community and in the wider world, can be enhanced. It is grounded in richly illustrated examples of sociolegal researchers working in design mode, including original individual and collaborative experiments involving a total of over 200 researchers and of experts from subfields such as social design, policy design and speculative design working on issues of sociolegal concern. It closes with an opening--a set of accessible sociolegal design briefs on which the impatient can make an immediate start. Written by an experienced sociolegal researcher with formal training in graphic design, the book is primarily focused on what the sociolegal research community can take from design, but it also offers lessons to designers, especially those who work with law.
OCLC-licensed vendor bibliographic record.
Keywords: LAW / General; LAW / Legal Writing; Sociological jurisprudence -- Research; Design